ZnO/MgO distributed Bragg reflectors - Huo, Bingzhi; Hu, Lizhong; Zhang, Heqiu; Zhao, Ziwen; Fu, Qiang; Chen, Xi (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
ZnO/MgO distributed Bragg reflectors (DBRs) are grown by pulsed laser deposition. DBR samples grown at the same temperature and the same pressure show obvious reflections in transmission spectra. If there is a standing wave in the ZnO layers, it is evident that the full width at half maximum of the ZnO peak in photoluminescence spectra could be decreased when the sample reflects more photons whose wavelength is about 380 nm.
Optica Applicata, Vol. 39, 2009, nr 1, s. 169-174
Keywords: optyka; zinc compounds; semiconducting II-VI materials